Segar Dimsum online ordering system for agents / Nur Khairunnisa Kamarol Zaman - Kamarol Zaman, Nur Khairunnisa (2023)
Segar Dimsum Online Ordering System (SDOOS) for Agents is a computerized system that helps in the order management process at Segar Dimsum. During the early stages of development, Segar Dimsum's problems were identified. As a result, the SDOOS was created to improve the current business process and ease critical problems. The SDOOS also helps in order management by saving agents time when placing product orders and completing the overall ordering process. A computerized system also assists admin and staff in handling orders more efficiently. This system is the result of a development process that used the SDLC's Waterfall Model. The methodology is divided into six stages: planning, analysis, design, development, testing and evaluation, and documentation. Furthermore, the Ten Usability Heuristics are used as a theory that serves as a guideline for the developer when developing the SDOOS. To evaluate system functioning, the test case and system flow are utilized to ensure that the system works as planned. Furthermore, the Usability Metric is utilized to validate user evaluations by assessing the system's usability. This system was reviewed by two experts and ten potential users, and their comments were taken into consideration. All recommendations and enhancements acquired during the testing session can be utilized as a guideline for future work to improve the system's functionality and usability.